Shining a Light on Policing of the Dark Web: An Analysis of UK Investigatory Powers. (October 2020) - Davies, Gemma
The dark web and the proliferation of criminals who have exploited its cryptographic protocols to commit crimes anonymously has created major challenges for law enforcement around the world. Traditional policing techniques have required amendment and new techniques have been developed to break the dark web's use of encryption. As with all new technology, the law has been slow to catch up and police have historically needed to use legislation which was not designed with the available technology in mind. This paper discusses the tools and techniques police use to investigate and prosecute criminals operating on the dark web in the UK and the legal framework in which they are deployed. There are two specific areas which are examined in depth: the use of covert policing and hacking tools, known in the UK as equipment interference. The operation of these investigatory methods within the context of dark web investigations has not previously been considered in UK literature, although this has received greater analysis in the United States and Australia. The effectiveness of UK investigatory powers in the investigation of crimes committed on the dark web are analysed and recommendations are made in relation to both the law and the relevant Codes of Practice. The article concludes that while the UK has recently introduced legislation which adequately sets out the powers police can use during online covert operations and when hacking, the Codes of Practice need to specifically address the role these investigative tools play in dark web investigations. Highlighted as areas of particular concern are the risks of jurisdiction forum shopping and hacking overseas. Recommendations are made for reform of the Investigatory Powers Act 2016 to ensure clarity as to when equipment interference can be used to search equipment when the location of that equipment is unknown.